Potebnia and Skovoroda: Catching an Elusive Bird - Ушкалов, Леонід Володимирович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article shows how Hryhorii Skovorada’s ideas are recepted by Oleksandr Potebnia in his works. It is emphasized that the basis of Potebnia’s understanding of Skovoroda’s philosophy is the following thesis: “Skovoroda fully realized the relativity of knowledge. However, in relativity of knowledge terms, he consideredt it possible to cognize the truth by studying its symbols, which exist in nature and human mind”. This thesis affirms that Potebnia correlates his own cognitive theory with the one introduced by Skovoroda.